2017
DOI: 10.1155/2017/5957107
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Adaptation of Water-Based Restoratives Placed as Liners under a Resin Composite

Abstract: Purpose. To investigate the cavity adaptation of mineral trioxide (ProRoot MTA/MT), tricalcium silicate (Biodentine/BD), and glass ionomer (Equia Fil/EF) cements used as liners and the interfacial integrity between those liners and a composite resin placed as the main restorative material. Materials and Methods. Standardized class I cavities (n: 8 per group) were prepared in upper premolars. Cavities were lined with a 1 mm thick layer of each of the tested materials and restored with Optibond FL adhesive and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…Marginal sealing (studied with microleakage studies) and shear-bond strength (SBS) are 2 properties that have to be evaluated to indicate the use of a dentin substitute [ 12 13 ]. Although the use of Biodentine has been validated following several studies evaluating the interfaces, SBS and marginal adaptation in an “open sandwich” technique, there is still limited information on leakage [ 9 14 15 16 17 18 19 20 21 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Marginal sealing (studied with microleakage studies) and shear-bond strength (SBS) are 2 properties that have to be evaluated to indicate the use of a dentin substitute [ 12 13 ]. Although the use of Biodentine has been validated following several studies evaluating the interfaces, SBS and marginal adaptation in an “open sandwich” technique, there is still limited information on leakage [ 9 14 15 16 17 18 19 20 21 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cracks, the bulk of GIC contains pores. Porosity, defined as the presence of empty spaces inside [48] μCT Wet (100% RH), 37°C, 48 h.…”
Section: Structural Integrity Of the Bulkmentioning
confidence: 99%
“…Yes (1) C, A (2) No the bulk of GIC, was reported in 11 studies [48,51,53,59,62,64,66,71,74,76,78], but it was sometimes identified as "voids," "air bubbles," or "air inclusions." Three out of the 11 studies measured the porosity in the bulk of the restorations in either 3D [48] or 2D [59,62]. A μCT-based study by Abraham et al [48] used silver nitrate infiltration to quantify the 3D percentage of porosity in entire fillings reporting a 0.88% prevalence.…”
Section: Nomentioning
confidence: 99%
See 1 more Smart Citation
“…The manufacturer claims that the products iRoot-BP and iRoot-BP Plus are insoluble, radiopaque, need moisture to set and do not shrink during setting. However, recent results showed iRoot-SP as very soluble that does not fulfill the ANSI/ADA Specification 57/2000 [54].…”
Section: Physico-chemical Properties Of Cs Cementsmentioning
confidence: 99%